Magnetic order and local field distribution in the hybrid magnets [FeCp*(2)][MnCr(ox)(3)] and [CoCp*(2)][FeFe(ox)(3)]: a muon spin relaxation study - Lancaster, T; Blundell, S; Pratt, F; Coronado, E; Galan-Mascaros, JR (2004)
Zero-field muon spin relaxation (μ+SR) measurements on materials from the series [ZIIICp*2][M IIMIII(ox)3] show precession signals at several frequencies, characteristic of quasistatic magnetic fields at up to three distinct muon sites.